Closed Beta Testing on Filariasis Treatment Monitoring Applications - Eko Budi Susanto; Paminto Agung Christianto; Mohammad Reza Maulana; Nur Fadhilah (International Journal of Information Technology and Business, 2023)
Monitoring applications for filariasis treatment have been developed to overcome the problem of elephantiasis or filariasis, one of which is the lack of monitoring during the distribution of elephantiasis medicines. One of the stages of application development is testing. Testing is conducted to ensure the application is ready to be implemented. In this study, closed beta testing was conducted to determine the feasibility of the application. The results of the validity test and reliability test showed that the results obtained were that all items on the questionnaire were declared valid and reliable. While the results of the feasibility test on the questionnaire results stated that the application was very feasible to be implemented.